Synthesis of peptides with cysteine sulfinic acid via the cysteine methoxybenzyl sulfone. Issue 2 (6th October 2019) - Urmey, Andrew R.; Zondlo, Neal J.
Abstract: Cysteine sulfinic acid is a protein posttranslational modification that is formed under oxidative conditions and is regulated both enzymatically and nonenzymatically. Cysteine oxidation to the sulfinic acid has been observed broadly throughout the proteome and can induce activation or inhibition of function in proteins. Recently, wide‐scale, reversible regulation of the sulfinic acid state of cysteine within proteins was identified, posing new questions in cysteine sulfinic acid biology. Existing methods to synthesize peptides with cysteine sulfinic acid can suffer from low yield, due to the formation of side products in the disulfide, sulfenic acid, and/or sulfonic acid oxidation states. Herein, a method for the synthesis of peptides with cysteine sulfinic acids was developed, via protection of cysteine sulfinic acid as the methoxybenzyl (Mob) sulfone. Cysteine Mob sulfone was synthesized as an Fmoc amino acid in one step from the commercially available Mob‐protected Fmoc‐cysteine (Fmoc‐Cys(Mob)‐OH). This amino acid was directly incorporated into peptides via solid‐phase peptide synthesis. Alternatively, peptides were synthesized using Fmoc‐Cys(Mob)‐OH, followed by subsequent oxidation within peptides of the thioether to the Mob sulfone via H2 O2 and catalytic niobium carbide. Deprotection of peptides under strongly acidic conditions (50% triflic acid, 45% trifluoroacetic acid, 5% water) generated peptides with cysteine sulfinic acid. This approach was applied to the synthesis of peptides containing cysteine sulfinic acid within diverse peptide sequence contexts. Abstract :